Dioscin from Polygonatum sibiricum induces apoptosis and autophagy in Ishikawa human endometrial cancer cell and in vivo - Xiaoli Li; Runhui Ma; Zhijing Ni; Wei Wang; Kiran Thakur; Jianguo Zhang; Zhaojun Wei (Food Science and Human Wellness)
With an aim to comprehend the precise regulatory mechanism of dioscin against endometrial carcinoma (EC), we firstly extracted the components from Polygonatum sibiricum followed by identification and structural characterization. The anti-EC activity of dioscin was initially determined based on the inhibition of Ishikawa cell proliferation and tumor growth. The high-throughput sequencing data indicated that dioscin not only promoted apoptosis, including decrease of poly ADP-ribose polymerase (PARP) and B-cell lymphoma-2 (Bcl-2) and increase of c-PARP and Bcl-2-associcated agonist of cell death (Bad), but also induced autophagy, including increase of autophagic lysosomes and LC3Ⅱ/LC3Ⅰ ratio. Mechanistic exploration suggested that dioscin induced autophagy and apoptosis through inhibition of PI3K/AKT/mTOR signaling pathway. Besides, the dioscin-regulated p53 pathway was mainly involved in autophagy induction. Furthermore, inhibition of Ishikawa cell autophagy was linked to dioscin-induced apoptosis. Our data suggest the immense potential of dioscin for the development of functional food for EC and related medical application.